Geospatial differences in organic carbon stock, structural and hydraulic properties of a coarse-textured soil under oil palm plantation - Tochukwu, Amanze Chikamnele; Fransisca, Eluagu Kelechi; Kalu, Ibe Olughu; Ekeoma, Ukabiala Maduabuchi (Review of Plant Studies, 2025)
Cropping systems can impact changes in the physicochemical conditions of soils across a given landmass, thereby influencing decisions on management strategies for soils under such use. The research was carried out to ascertain the spatial variation of organic carbon stock, structural, and hydraulic properties of soil under oil palm plantation. The research was laid out in a randomized complete block design. Nine replicates each of disturbed and undisturbed soil samples were randomly collected from the area at a depth of 0 – 20 cm. Soil parameters were determined in a laboratory, and data obtained were analyzed for spatial variation using geographical information system software. Organic carbon stock varied from 40 – 65 tons/ha, bulk density varied from 1.15 – 1.35 mg/m³, saturated hydraulic conductivity varied from 2.70 – 3.05 cm/min, clay flocculation index varied from 64 – 70%, clay dispersion index varied from 30 – 36%, dispersion ratio varied from 5 – 25%, aggregated silt + clay varied from 16.5 – 20.5%, and mean weight diameter varied from 1.10 – 1.50 mm. Oil palm plantation influences the spatial condition of organic carbon stock and structural-hydraulic properties of soils under its coverage. Consequently, soil management strategies for the land must be designed to address the unique qualities of the various regions of the landmass.